Reasons for complementary therapies and characteristics of users among HIV-infected people - Agnoletto, Vittorio; Chiaffarino, Francesca; Nasta, Paola; Rossi, Roberto; Parazzini, Fabio (International journal of STD & AIDS, 2003)
The aim of this study was to analyse in a large sample of HIV-infected subjects the expectations toward complementary therapies (CT) and the characteristics of users. Self-administered anonymous questionnaires were distributed in seven European countries among HIV-infected subjects consecutively attending the offices of AIDS organizations. Among 632 ever CT users, nutritional supplements (124 subjects) and psycho-physiological approaches (116 subjects) were the most frequent CT used: 61.4% used CT to improve energy. Half the CT users wanted to prevent or alleviate the highly active antiretroviral therapy (HAART) side effects. General malaise and neuropathy were the most common HAART side effects, where CT users found improvement (62.0% and 54.7%, respectively). Acupuncture improved neuropathy in a high proportion of subjects (87.5%); whereas for others CT were considered less effective (range 20.0–36.4%). The most common expectations from CT were to improve energy and to prevent or alleviate the HAART side effects. This suggests that HIV-infected people expect not so much specific help as general support from CT.